The Importance of Balance Between Hard Skills and Soft Skills to Improve The Quality of Higher Education Graduates - Sandra, Jana; Suryana , Ade; Indrayanti , Sri (Mudir : Jurnal Manajemen Pendidikan, 2023)
The realm of employment holds the belief that exceptional human resources are individuals who not only possess technical skills but are also adept in the areas of interpersonal skills. The field of academia has also unveiled that, according to a study conducted at Harvard University in the United States, an individual's success is not solely determined by their knowledge and technical abilities (hard skills), but rather by their capacity to effectively manage themselves and others (soft skills). This study aims to address the significance of maintaining a balance between hard skills and soft skills in the professional world, as well as the necessary steps that tertiary institutions should take in order to adequately prepare their graduates. This is a qualitative study using a phenomenological methodology. Data gathering was conducted through open-ended interviews with HRD managers and students. The findings of the research indicate that there are still numerous higher education institutions that have not equipped students with knowledge or recognition of the significance of maintaining a harmonious blend of technical abilities and personal qualities to meet the requirements of the job market. Students should be provided with educational resources on intrapersonal and interpersonal skills, either through lectures or post-internship discussions.